2021
DOI: 10.1002/jbt.22980
|View full text |Cite
|
Sign up to set email alerts
|

Association of Type 1 diabetes with ulcerative colitis in BALB/c mice: Investigations on sex‐specific differences

Abstract: Diabetes comorbidity in ulcerative colitis (UC) has relevant clinical and therapeutic implications. The link between hyperglycemia and intestinal barrier function with respect to infection and inflammation consequences exists in diabetes. The present study was designed to decipher the molecular mechanisms associated with Type 1 Diabetes mellitus and the UC in both male and female BALB/c mice. Dextran sulfate sodium (DSS; 2.5%w/v) dissolved in drinking water was given for three cycles (each cycle; 7 days) with … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 48 publications
0
3
0
Order By: Relevance
“…Considering the sex difference in the proportion of those with an A classification, sex hormones likely have an impact not only on CD onset but also on disease progression. A study showed that hyperglycaemia exacerbated the pathological conditions in male animal models, while the female control group had a milder disease course ( Singla et al, 2021 ), supporting the potentially important role of sex hormones in disease development.…”
Section: Discussionmentioning
confidence: 97%
“…Considering the sex difference in the proportion of those with an A classification, sex hormones likely have an impact not only on CD onset but also on disease progression. A study showed that hyperglycaemia exacerbated the pathological conditions in male animal models, while the female control group had a milder disease course ( Singla et al, 2021 ), supporting the potentially important role of sex hormones in disease development.…”
Section: Discussionmentioning
confidence: 97%
“…A 24-well plate was seeded with cells and incubated for 24 h. Cells were subjected to respective treatments for 24 h, and then the TUNEL assay was performed according to the manufacturing instructions (Calbiochem, Oncogene Research Product). Images were captured using a fluorescence microscope and analyzed with ImageJ software. , …”
Section: Methodsmentioning
confidence: 99%
“…Images were captured using a fluorescence microscope and analyzed with ImageJ software. 53,54 3.13. Statistical Analysis.…”
Section: Drug Administration and Treatmentmentioning
confidence: 99%